Kleinschalige Beeldende Kunstopdrachten. - Lommen, Bart (Amsterdam : AFK (Het Amsterdams Fonds voor de Kunst), 1996)
Assmann, Gijs ; Wong, Sarah ; Ligteringen, Hans ; Berkhemer, Michael ; Polhuis, Gerard ; Dulk, Nico den ; Volger, Marc ; van der Ploeg, Jan ; van den Toorn, Joost ; Dings, Nicolas ; Cops, Marco ; Shaw, Jeffrey ; Oudshoorn, Rob ; Premsela, Benno ; Smulders, Godelieve ; Berger, Casper ; Groenendijk, Ewout ; Breed, Peter ; Kuchlein, Egon ; de Wint, Rudi van ; Veneman, Peer ; Lucas, Henri ; van Warmerdam, Marijke ; Schabracq, Alexander ; Postma, Tom ; Thiadens, Marc ; van Rouendal, Jaap ; van Lamsweerde, Inez ; Galgiani, Phillip ; Dolron, Désirée ; King, Lucia ; Spinhoven, Bill ; Veldhoen, Martijn ; Thijssen, Tony ; Nette, Adriaan ; de Jonge, Jaap ; Bogers, Peter ; Hoebink, Willem ; Salverda, Hilde ; Levano, Chaim ; Oudt, Bas ; Bons, Jan ; Blom, Ansuya ; Kolman, Stef ; Kolman, Selene ; Oosterhof, Frans ; De Koning, Nol ; de Visser, Bea ; Garcia, David ; Thoenes, Pieter ; Patchwork ; Immoos, Franz ; van der Horst, Robert ; Servaas ; Smeets, Jos
Nederlands
boek